Ali je sodna praksa glede 1. člena EKČP konsistentna? - Žiher, Aleš (Pravnik, 2014)
Questions as to whether a state is obliged to respect the European Convention on Human Rights outside its territory or not are asked more and more frequently in the era of globalism and fight against terrorism. The interpretation of Article 1 of the ECHR, which sets limits for its reach, is of vital importance - High Contracting Parties are according to the ECHR obliged to protect the people within their jurisdiction. The standpoint of the case-law is that the jurisdiction is primarily territorial, but there are three groups of exceptions: when a State has an effective overall control over an area, when it exercises an authority or control over an individual or when it exercises all or some public powers which leads to the violations of the ECHR in the course of the execution.
Keywords: človekove pravice; European Union; Evropska konvencija o varstvu človekovih pravic in temeljnih svoboščin; Evropska unija; human rights; kršenje; pristojnosti; sodna praksa